PERTANGGUNGJAWABAN TINDAK PIDANA BADAN HUKUM KORPORASI DALAM PERJUDIAN ONLINE DARI PENDEKATAN SISTEM PERADILAN PIDANA DI INDONESIA - Rivo Rizky Prahara; Joko Sriwidodo; Edi Saputra Hasibuan (Collegium Studiosum Journal, 2025)
Criminal liability for online gambling is regulated in the provisions of Article 45 paragraph (3) of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions. If a criminal act is committed by the Company, it is linked to the provisions of Article 52 paragraph 4 of Law Number 11 of 2008 concerning Electronic Information and Transactions, with a prison sentence plus two-thirds of the principal penalty. The objectives of this research are: first, to examine and provide legal solutions regarding criminal regulation of corporations in carrying out online gambling approaches from the criminal justice system in Indonesia; secondly, examining criminal responsibility for corporations in online gambling, the approach of the criminal justice system in Indonesia. The results of the research show that the prison sentence provisions in Article 45 paragraph 3 of Law Number 1 of 2024 are more severe than the criminal provisions in Article 45 paragraph 1 of Law Number 11 of 2008. There is a maximum limit of 10 (ten) years in Article 45 paragraph 3 of Law Number 1 of 2024, and 6 (six) years in Article 45 paragraph 1 of Law Number 11 of 2008. Despite this increase in prison sentences has increased, but the additional prison sentence period has not been maximized. The prison sentence should be increased further, so that it has a deterrent effect in enforcing the criminal law on online gambling. In fact, legislators should set a minimum limit for criminal perpetrators of online gambling.